The Correlation between Speaking Habit and Speaking Accuracy in Second Semester of English Department Student of UNISMA - Rizki Ika Saputri (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: English is the most commonly spoken language in the world and has become an important feature in all fields. Therefore, many individuals in daily life want to understand and use it. There are many ways that you can practice speaking English, such as making a habit of speaking. The objective of this study was to know whether there is correlation between speaking habit and speaking accuracy in second semester of English department student of UNISMA in the academic year 2019/2020. Correlation design is the design of this study with the population consisted of 30 students of second semester of English department student taken randomly. The instruments to collect the data were questionnaire and test. Questionnaire is used to collect the speaking habit data while the test is used to collect the speaking accuracy data. Person Product Moment formula is used by the researcher to find the coefficient correlation of the variables. The result of the study showed that there is no significant correlation between speaking habit and speaking accuracy. The data express that t-value of correlation between speaking habit and speaking accuracy is 0.295 higher than 0.05. It can be concluded that there is no correlation between speaking habit and speaking accuracy in second semester of English department student of UNISMA in the academic year 2019/2020. keywords: Correlation, Speaking Habbit, and Speaking Accuracy